Behavior of Woman Prostitutes for Conseling and Testing of HIV - Suryani Suryani; Ruwayda Ruwayda; M. Dody Izhar (Aloha International Journal of Health Advancement (AIJHA), 2019)
The high prevalence of current HIV/AIDS problems is not only a health problem of infectious disease, but has become a very widespread public health problem, one of the high risk groups is Female Sex Workers. The number of female sex workers who counsel and test HIV in Rawasari Health Center is still low that is 27.67%. This research was quantitative research with cross sectional design, using systematic random sampling technique with sample size of 77 female sex workers. Data were collected using questionnaire, then analyzed using Chi square test. The result showed that there was significant correlation between knowledge (p-value = 0.000), attitude (p-value = 0.000) and the role of health officer (p-value = 0.013) with the behavior of woman prostitutes in conducting HIV counseling and testing. It is hoped that health officers at Rawasari will improve direct and periodic counseling through information media, encourage and encourage female sex workers to conduct HIV counseling and testing. Keywords: knowledge; attitude; role of health officer; behavior; HIV counseling: HIV test